Spillovers in Education Choice - Juanna Schrøter Joensen; Helena Skyt Nielsen (Institute of Labor Economics (IZA), 2017)
This paper examines how skills are shaped by social interactions in families. We show that older siblings causally affect younger sibling's education choices and early career earnings. We focus on critical course choices in high school and overcome the identification challenges of estimating spillover effects in education by exploiting exogenous variation in choice sets stemming from a pilot program. The pilot induced an essentially random subset of older siblings to choose advanced math-science at a lower cost, while not directly affecting the course choices of younger siblings. We find that younger siblings are 2-3 percentage points more likely to choose math-science if their older sibling unexpectedly could choose math-science at a lower cost. We argue that the main influence of the pilot program on the younger siblings may be attributed to the social influence of the older sibling. Spillovers are strongest among closely spaced siblings, in particular brothers, and they have a lasting impact on the career out-comes of younger brothers. We argue that competition is likely one of the driving forces behind younger siblings conforming to their older siblings' choices.
Keywords: I21; I24; J24; 330; high school curriculum; siblings; social interaction; skill formation